The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.21273/hortsci.45.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Cultivated Grape with Native Perennial Grasses Nodding Needlegrass or California Barley as Cover Crops

Abstract: Two California native perennial grasses, nodding needlegrass [Nassella cernua (Stebbins & R.M. Love) Barkworth] and California barley [Hordeum brachyantherum Nevski ssp. californicum (Covas & Stebbins) Bothmer, N. Jacobsen & Seberg], were compared with a conventional grass cover crop, ‘Blando’ brome (Bromus hordeaceus L.), as well as resident (weedy) vegetation and a clean cultivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This result can be attributed to the fact that the regular mulching of alfalfa cover crop biomass led to decomposition and produced enough organic N to help meet the nutritional needs of trees. This assumption is supported by Wilson et al (2010), who reported that mowing alfalfa groundcovers once every 3 weeks returned an average of 2.5 tÁha -1 of green manure to the ground, corresponding to 85 kgÁha -1 of accumulated organic N. Positive groundcover effects have been reported in cultivated grapes (Costello, 2010) and several other fruit-based agricultural cropping systems (Radovich et al, 2009). The finding is also in line with Kuhn and Pedersen (2009) who reported that a cover crop-based system with regular mulching produced vigorous tree growth and significantly higher tree productivity.…”
Section: Discussionmentioning
confidence: 80%
“…This result can be attributed to the fact that the regular mulching of alfalfa cover crop biomass led to decomposition and produced enough organic N to help meet the nutritional needs of trees. This assumption is supported by Wilson et al (2010), who reported that mowing alfalfa groundcovers once every 3 weeks returned an average of 2.5 tÁha -1 of green manure to the ground, corresponding to 85 kgÁha -1 of accumulated organic N. Positive groundcover effects have been reported in cultivated grapes (Costello, 2010) and several other fruit-based agricultural cropping systems (Radovich et al, 2009). The finding is also in line with Kuhn and Pedersen (2009) who reported that a cover crop-based system with regular mulching produced vigorous tree growth and significantly higher tree productivity.…”
Section: Discussionmentioning
confidence: 80%
“…In the current study, if the higher in-row soil moisture in the nodding needlegrass treatment means that these vines used less in-row water, this should have been reflected in a smaller vine canopy, i.e., having lower vigor, than under clean cultivation. However, the vines in the nodding needlegrass and clean cultivation treatments had equivalent pruning weights, which is an index of vigor and canopy size, and vine trunk diameter was greater in the nodding needlegrass treatment compared with clean cultivation (Costello, 2010). There is therefore little evidence that lower vine water use explains the higher inrow soil moisture content in the nodding needlegrass treatment.…”
Section: Discussionmentioning
confidence: 94%
“…If the vine roots were located primarily in the in-row zone as has been shown for drip-irrigated vineyards (Stevens and Douglas, 1994), the extra water use by the nodding needlegrass cover crop in the between-row zone, occurring primarily during the off-season, should have had little effect on vine growth or yield. Indeed, this was the case, because yield and pruning weight with nodding needlegrass as a cover crop was equivalent with clean cultivation (Costello, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations